The Influence Of Peer Social Environment On Students Learning Strategies And Academic Achievement At Jakarta State University - imelda bekay zharya; Christian Wiradendi Wolor; Darma Rika Swaramarinda, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to determine the Influence of Peer Social Environment on Learning Strategies and Academic Achievement of Jakarta State University Students. In the world of education, one indicator of the success of a university is the academic achievement of students. One of the many factors that can influence academic performance is the peer social environment. The peer social context can have a significant impact on individual performance, including in terms of learning strategies. Peers can serve as a source of inspiration, support, or even pressure that can influence the learning strategies considered by students. This study uses a quantitative method with a correlational design. The research sample was taken from students of Jakarta State University. Data were collected through questionnaires and analysis using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results of this study indicate that there is a significant positive influence between the peer social environment and students' learning strategies and academic achievement. So it is hoped that the findings of this study can contribute to a better understanding and also provide insight into the development of programs aimed at improving academic achievement among students.